1998
DOI: 10.1359/jbmr.1998.13.11.1668
|View full text |Cite
|
Sign up to set email alerts
|

Heterocycle-Containing Bisphosphonates Cause Apoptosis and Inhibit Bone Resorption by Preventing Protein Prenylation: Evidence from Structure-Activity Relationships in J774 Macrophages

Abstract: Recent evidence suggests that bisphosphonates (BPs) may inhibit bone resorption by mechanisms that lead to osteoclast apoptosis. We have previously shown that BPs also reduce cell viability and induce apoptosis in the macrophage-like cell line J774. To determine whether BPs inhibit osteoclast-mediated bone resorption and affect J774 macrophages by the same molecular mechanism, we examined the potency to reduce J774 cell viability of pairs of nitrogen-containing BPs that differ slightly in the structure of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
157
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 239 publications
(169 citation statements)
references
References 41 publications
7
157
0
5
Order By: Relevance
“…Therefore, the ability of pamidronate to down-regulate bcl-2 expression further suggests the involvement of caspase activation with changes in mitochondrial function in this pathway. Luckman and colleagues have reported that aminobisphosphonates induce apoptosis in a mouse macrophage cell line via inhibition of the mevalonate pathway and inhibition of protein prenylation (Luckman et al, 1998). A similar pathway has been identified for induction of apoptosis in human myeloma cells by YM 175 (Shipman et al, 1998).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, the ability of pamidronate to down-regulate bcl-2 expression further suggests the involvement of caspase activation with changes in mitochondrial function in this pathway. Luckman and colleagues have reported that aminobisphosphonates induce apoptosis in a mouse macrophage cell line via inhibition of the mevalonate pathway and inhibition of protein prenylation (Luckman et al, 1998). A similar pathway has been identified for induction of apoptosis in human myeloma cells by YM 175 (Shipman et al, 1998).…”
Section: Discussionmentioning
confidence: 91%
“…Assessment of Viable Cell Number by MTT Assay-The number of viable J774 macrophage cells was determined by MTT assay as previously described (23). J774 cells were seeded at a density of 10 4 cells/well into 96-well plates and then treated with RIS, NE10790, or NE10485 the following day in replicates of six wells.…”
Section: Methodsmentioning
confidence: 99%
“…There is a strong structureactivity relationship such that changes to the structure of the nitrogen-containing R 2 side chain or to the phosphonate groups, which alter antiresorptive potency, also influence the ability to inhibit protein prenylation to a corresponding degree. 72 An important verification of the critical importance of this pathway has come from showing that the addition of intermediates of the mevalonate pathway (such as FPP and GGPP) could overcome bisphosphonate-induced apoptosis and other events in many cell systems. Another prediction was that if inhibition of the mevalonate pathway could account for the antiresorptive effects of bisphosphonates, then the statin drugs should also inhibit bone resorption.…”
Section: Figurementioning
confidence: 99%